Deceptive measures of progress in the NHS long-term plan for cancer: case-based vs. population-based measures - Oke, JL; Brown, SJ; Senger, C; Welch, HG (Springer Nature, 2023)
The NHS Long Term Plan for cancer aims to increase early-stage diagnoses from 50% to 75% and to have 55,000 more people each year survive their cancer for at least 5 years following diagnosis. The targets measures are flawed and could be met without improving outcomes that really matter to patients. The proportion of early-stage diagnoses could increase, while the number of patients presenting at a late-stage remains the same. More patients could survive their cancer for longer, but lead time and overdiagnosis bias make it impossible to know whether anyone had their life prolonged. The target measures should switch from biased case-based measures to unbiased population-based measures that reflect the key objectives in cancer care: reducing late-stage incidence and mortality.